Trading millet and sorghum genetic resources women vendors in the village fairs of San and Souentza, Mali - Smale, Melinda; Diakité, Lamissa; Dembélé, Brahima; Traoré, Issa Seni; Guindo, Oumar; Konta, Bouréma (International Food Policy Research Institute, 2008)
In Mali, liberalization of seed markets for sorghum and millet, the staple food crops, has not advanced at the same rate or with the same measurable success as liberalization of grain markets. Most seed of these crops is uncertified and continues to be supplied to farmers by farmers, according to clan and ethno-linguistic group. After poor harvests or when replanting after a dry spell, farmers rely on local markets for grain as sources of seed. This paper summarizes the findings of a vendor survey conducted in two marketsheds during weekly fairs. No certified seed is sold. Almost all vendors are women who are also farmers. Variety integrity is maintained particularly for millet seed in the marketshed of the Sahelian zone, where the range of variety adaptation is very limited. Grain that is suitable for seed is brought to market directly from granaries. Varieties are identified by their provenance. Socially prescribed behavior is apparent in price-fixing, price discounts, procurement practices, and the spatial organization of vendors. Preliminary hypotheses are tested with a simple regression. Marketshed, which is highly correlated with the ethnic composition of the population, agro-ecology, market infrastructure and crop sold, has a dominant impact on quantities sold. Quantities sold do not respond to expected prices. Greater specialization of the vendor in trade as compared to farming, younger age, and additional years in school positively influence amounts sold. A better comprehension of this type of trade could contribute to policies that improve the access of poor farmers to valuable crop genetic resources, enhancing their seed security and productivity.